A comparative study of the economic and environmental benefits in the use of green building technology and traditional building construction / Zarul Azhar Nasir, Mohd Samsudin Abdul Hamid and Adhilla Ainun Musir - Nasir, Zarul Azhar; Abdul Hamid, Mohd Samsudin; Musir, Adhilla Ainun (2012)
This study is a comparative study of methods used in the construction sector. More specifically, it examines the economics and environmental benefits in the use of green building technology and traditional building construction. The first section gives a detailed discussion of the concept, technique and system implemented by both methods. Second section highlights on the empirical literature review done on green building benefits. The third section will present the impact on the cost elements of each method includes the rental property income, sales price, operating cost, environment cost, public infrastructure costs, financing costs, building costs, development costs and design costs.